The Wounded Self: Anorexia Nervosa and Pathological Narcissism: How the Daughter May Be Used as a Parental Selfobject and How This May Impact Upon Her Development of Self and May Predispose Her to the Development of Anorexia Nervosa and Implications - Bliss, Rhonda (Auckland University of Technology, 2004)
This study explores how the use of the daughter as a parental selfobject may impact on the daughter’s development of self and how this may predispose her to the development of anorexia nervosa and implications for treatment. The method is a modified systematic literature review. This study explores the self psychology model which describes the daughter who develops anorexia nervosa as a narcissistic selfobject used by one or both parents. In the absence of empathic responsiveness to her selfobject needs, and as she functions as a parentified child, there may be an arrest in her self development with ensuing deficits of self structure. Her lack of internal self structure and self regulation render the self susceptible to fragmentation and depletion. Disappointed and frustrated by her failure to get her selfobject needs met by human beings, at a time of stress such as adolescence, she may turn to anorexia to meet her selfobject needs. Anorexia, therefore, is seen in the self psychology model as representative of a disorder of self and anorexic symptoms as attempts to supply missing selfobject functions. There was found to be support for the self psychology understanding of parent-child relationships in the wider eating disorder literature. The findings of empirical studies and a grounded theory study support the self psychology understanding that these women have an interpersonal style of being invested in meeting the needs of others. Findings suggest that the development of anorexia may be a response to difficulties in self development and related to a loss of ability to sustain a sense of self. The findings generally support a link between the daughter’s experience as a self object, her resulting self structural deficits and the development of anorexia. Implications for treatment are discussed and recommendations made for future research.
Keywords: Anorexia nervosa; Psychotherapy; Parent and child; Psychological aspects